A research modeling to understand online shopping intention - Delafrooz, Narges; Paim, Laily; Khatibi, Ali (American-Eurasian Network for Scientific Information, 2011)
This study aims to shed light on the antecedents relating to the extent of both the attitude toward online shopping and the purchase intention. This work is done from an integrated research framework based on the Attitude Model and the Theory of Planned Behavior (TPB). A total of 370 randomly selected respondents from the states of Selangor, Malaysia answered the questionnaire and the data was analyzed using path analysis to identify the possible predictors. The results support the use of the construct "attitude toward online shopping" as a bridge to connect the Attitude Model and the Behavioral Intention Model to establish an integrated research framework and to shed light on how consumers form their attitudes toward online shopping and make purchase intention. Online retailer should provide more benefits than ever before, with the consequence that consumers will hold a more positive attitude toward online shopping that leads to their purchase intentions. In summary, online retailers need to ensure that the online shopping process through their websites should be making as easy, simple and convenient as possible for consumers to shop online. The websites should also be designed in such a way that they are not too confusing for potential new buyers, particularly among consumers, who may not be familiar with this new form of shopping. In addition, online retailers need to provide a competitive price for products in order to attract online shoppers to their websites and encourage them to make purchase decisions. This study pioneers in building an integrated research framework to understand how consumers form their attitudes toward online shopping and make purchase intention.